Pengaruh Penggunaan Media Sosial dan Dukungan Sosial terhadap Kesehatan Mental Generasi Z dengan Mediasi Self-Esteem - Sinollah Sinollah; Fetty Desi Ariyanti; Laura Diva Al Fadila; Wardatul Mu’mila (Fakultas Ekonomi dan Bisnis, Universitas Islam Raden Rahmat Malang, 2026)
The rapid growth of social media usage among Generation Z has significantly influenced their psychological dynamics, particularly self-esteem and mental health. This study aims to analyze the effects of social media use and social support on mental health, with self-esteem positioned as the mediating variable. A quantitative explanatory survey design was employed involving 105 respondents aged 18–25 years. Data were collected through an online questionnaire and analyzed using Structural Equation Modeling (SEM). The findings indicate that social media use does not significantly affect either self-esteem or mental health. In contrast, social support has a significant positive effect on self-esteem, and self-esteem significantly predicts mental health. Furthermore, self-esteem acts as a significant mediator between social support and mental health, but does not mediate the relationship between social media use and mental health. These results highlight that self-esteem is a key psychological factor influencing the mental well-being of Generation Z. Therefore, strengthening self-esteem through digital literacy, supportive social environments, and appropriate psychological interventions is essential to enhance youth mental health in the digital era